Development of a Google Sites-Based Escape Room Media in Science Learning for Grade VIII Junior High School - Syamsuriyani; Firdaus Daud; Halimah Husain; Muhiddin Palennari; Muhammad Arsyad (Jurnal Penelitian Pendidikan IPA, 2026)
This study was motivated by challenges in science learning, particularly the Human Circulatory System material, which is often perceived as abstract and complex, leading to low student motivation and engagement. The research aimed to develop a valid and practical digital learning medium using a game-based Escape Room concept for junior high school students. This Research and Development (R&D) study applied the ADDIE model, involving material experts, media experts, 15 science teachers, and 23 eighth-grade students. Data were collected through questionnaires, observations, and interviews. The results showed that the developed media was highly valid, with material expert scores increasing from 76% to 85% and media expert scores from 73.3% to 86.7% after revisions. The media was also considered highly practical by teachers (86.3%), although internet stability was noted as a challenge. Students responded very positively, with a score of 91.9%. Qualitative findings revealed that the “Detective Mission” narrative enhanced classroom engagement, encouraged collaboration, and stimulated critical thinking. In conclusion, the Google Sites-based Escape Room is a feasible and effective innovative medium for visualizing abstract science concepts and supporting the development of students’ critical thinking and collaboration skills.